Geology, alteration and precious metal reconnaissance of the Nogal Canyon area, San Mateo Mts., N.M. - Foruria, Jon, author (Colorado State University. Libraries, 1984)
The Nogal Canyon area lies within the southern San Mateo mountains and displays epithermal, volcanic hosted precious metal occurrences in the San Jose and Quartz Hill districts and in the Aragon Hill area. The San Mateos represent an isolated, north trending, eastward tilted, structural block located in the northeastern portion of the Cenozoic Mogollon-Datil volcanic field. Mid-Tertiary, calc-alkalic andesites to high silica rhyolites and minor volcaniclastics dominate the lithologies exposed in the Nogal Canyon area. The Oligocene Spears Formation, the oldest unit present, consists of andesitic to latitic flows, breccias, and ash-flow tuff and sporadic volcaniclastic sandstone. The Hells Mesa rhyolite ash-flow tuff overlies the Spears Formation and is sequentially superimposed by the Unit of Luna Park which includes andesitic flows, dacite flow breccias, rhyolite tuff, and minor volcaniclastics. The majority of the upper felsic sequence exposed in the southern San Mateos consists of the Oligocene Vicks Peak Tuff, a thick, densely to partially welded rhyolite ash-flow tuff, and the overlying Springtime Canyon Quartz Latite. Younger porphyritic rhyolite intrusives, rhyolite flow-dome rocks, and intrusive breccia appear localized along major structural trends within the southern foothills of the San Mateo mountains. Major northeast and northwest trending, steeply dipping, normal faults crosscut the Vicks Peak Tuff and host "fissure type" precious metal occurrences in the San Jose district. Structural preparation relates either to the proposed Nogal Canyon cauldron or to mid-late Tertiary regional extensional tectonism. Hydrothermal alteration effects contemporaneous with precious metal mineralization consist of pervasive and veinlet silicification, pervasive intermediate arqillic alteration, and quartz-alunite replacement alteration. Silica alteration is strongly localized along fracture and breccia zones consisting of vein-infillings, pervasive wall rock alteration, and quartz network-stockwork type occurrences. The gangue mineral assemblage accompanying vein-infilling silicification includes adularia, sericite, calcite, pyrolusite, and cryptomelane. Intermediate argillic alteration consists of montmorillonite, montmorillonite-illite mixed layer, illite, kaolinite, and pyrite systematically zoned as reaction aureoles about major structures. Argillic alteration broadens beneath the Vicks Peak Tuff-Springtime Canyon Quartz Latite contact which acted as a permeability barrier to ascending hydrothermal solutions. Quartz-alunite alteration occurs as a really restricted, pervasive replacement deposits with accessory pyrite, specularite, kaolinite, and chalcedony. Mineralization accompanying vein-related silicification consists of native silver, native gold, cerargyrite, and pyrite and appears modified by supergene oxidation processes. Trace element studies indicate the mineralization exhibits low arsenic and antimony signatures and lacks base metal introduction at present erosional levels. A single hydrothermal episode which generated structurally confined boiling appears responsible for the development of hypogene alteration and insignificant silver-gold mineralization centered over the Nogal Canyon area. Precious metal occurrences at Aragon Hill consist of gold bearing, quartz-calcite-barite fracture fillings crosscutting the Aragon Hill intrusive breccia. Pervasive phyllic alteration, contemporaneous with breccia emplacement, occurs throughout the pipe-like intrusive breccia and concentrically envelopes the surrounding rhyolite flow-dome rocks. Phyllic alteration consists of sericite, montmorillonite-chlorite mixed layer clay, quartz, pyrite, and kaolinite products. The precious metal bearing fracture fillings probably represent leaching and minor metal deposition during the late waning stages of breccia emplacement, or possibly high level expression of epigenetic breccia-hosted silver-gold mineralization at depth.
Keywords: Geology -- New Mexico -- Socorro County; Mines and mineral resources -- New Mexico -- Socorro County